PENDEKATAN TEORI BELAJAR ANDRAGOGI TERHADAP KEMAMPUAN MENYELESAIKAN SOAL MATEMATIKA DITINJAU DARI GENDER - Yuni Rosania; Mujib Mujib; Fraulein Intan Suri (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
The purpose of this study was to see the effect of the andragogical learning theory approach on students' ability to solve mathematical questions in terms of student gender. This type of research is a quantitative study with an experimental method. The population of this study was all class X of SMA N 14 Bandar Lampung Academic Year 2018/2019. The sampling technique in this study used cluster random sampling. The analysis technique used in this study is a two-way variance analysis with cells not equal to a significant level of 5%. Based on the results of two-way variance analysis with unequal cells, it was found that: (1) there was an influence of andragogical learning theory approach on students 'ability to solve mathematical questions, (2) there was a gender influence on students' ability to solve math problems, (3) there was no interaction between andragogical learning theory approach with gender on students' ability to solve math problems